A case of ameloblastoma in a child suspected dentigerous cyst - FUKUZAWA, Shinya; ICHIHARA, Sachiko; IMAI, Takao; KURITA, Kenichi; NAKATSUKA, Kensuke (Pediatric Oral and Maxillofacial Surgery, 2005)
We report a case of ameloblastoma in left second molar region of the mandible of a child. The ameloblastoma is relatively common benign odontogenic tumor most often located in the mandible. Many of the patients are young adults in the second decade of life. Radiographs usually show multilocular radiolucent lesion in most cases; however, sometimes demonstrate a unilocular radiolucency and a differential diagnosis from an eruption cyst and a dentigerous cyst becomes increasingly difficult. Thus, in certain factors, many cases may be the result in misdiagnosis of these other diseases and still be lurking. Therefore, the difficulty of diagnosis and the importance of the preoperative biopsy for ameloblastoma may be indicated.